Neurociência e educação: por que sim? Por que não? - Coelho, Daniela Maria Valerio [UNIFESP] (2019)
This research aimed to investigate the knowledge that educators have about neuroscience, positive and negative aspects in the integration between the results of scientific research and knowledge produced in education, its applicability and possibilities. This is a descriptive study, conducted through an online survey, with a sample of 1643 educators, divided into 2 subgroups, according to the answer to the question “Do you consider yourself a neuroscience expert?”, namely: Educators without knowledge in neuroscience (ES) - 589 participants; Educators with knowledge in neuroscience (EC) - 1054 participants; As main results, this research presents data related to educators' knowledge about the neuroscience theme. In general, for all variables, a significant difference was observed between the group of educators with knowledge in neuroscience (EC) and educators without knowledge (ES). Regarding the level of knowledge in neuroscience, the group of EC 35.5% considered themselves with reasonable or good knowledge (92%); while surprisingly in the higher education group, 11% said they had reasonable and / or good knowledge on the subject. Regarding the participants' interest in the subject, 77% of the EC reported that they were always interested in neuroscience-related topics, while only 17% of the ES agreed with this statement. Even educators who have never been interested in neuroscience have found it fundamental after knowing it (67% of EC vs. 31% of ES). Overall, as regards teaching methods involving neuroscience and traditional methods, 83% of the ES group agree that conventional teaching methods are superior to those that include knowledge about neuroscience vs. 19% of the EC group. Regarding the need for neuroscience contents to be taught more systematically at undergraduate level, more than half of the EC group (69.5%) agree with this initiative vs. 39% of ES. Taken together, the data from this study show the importance of consistent neuroscience training for education professionals to be able to transpose the results of research on brain functioning to seek more innovative and intentional school practices, optimizing and consolidating knowledge. from the students.